Maximizing productivity, profitability and water use efficiency in Indian mustard (Brassica juncea) through hydrogel and salicylic acid - KUMAWAT, PRIYANKA; RAM, MANOHAR; KUMAR, PANKAJ; KUMARI, VARSHA; KHEDWAL, RAJBIR SINGH (The Indian Journal of Agricultural Sciences, 2024)
Addressing water scarcity in the arid and semi-arid regions of Rajasthan presents a substantial challenge to improve the productivity of Indian mustard [Brassica juncea (L.) Czern.]. The limited availability of water in these areas results in reduced yields of Indian mustard. Therefore, a field experiment was conducted during rabi (winter) seasons of 2018–19, 2019–20 and 2020–21 at the research farm of Sri Karan Narendra Agriculture University, Jobner, Rajasthan, to evaluate the impact of hydrogel and foliar application of salicylic acid on the growth, yield, economic returns and water use efficiency of Indian mustard. The results revealed that the application of hydrogel at a rate of 5.0 kg/ha, in combination with salicylic acid at a concentration of 200 ppm during the flowering and siliqua formation stages through foliar spray, had a significant and highly effective impact. This treatment displayed superior performance across a range of parameters, including growth characteristics, yield attributes, seed yield (1840 kg/ha), stover yield (3847 kg/ha), water use efficiency (8.53 kg/ha-mm), protein content (18.6%), oil content (39.13%), net returns (₹51,710/ha) and benefit-cost ratio (2.03). Furthermore, treatments involved 5.0 kg/ha of hydrogel in conjunction with 100 ppm of salicylic acid, as well as 2.5 kg/ha of hydrogel with 200 ppm of salicylic acid, produced similar results. The combined findings of this experiment endorse the application of hydrogel and salicylic acid as a sustainable and effective strategy for enhancing the productivity, profitability and water use efficiency of Indian mustard in the arid and semi-arid regions of Rajasthan.